The Effect of Knowledge and Attitude to Implement Dysmenorrhea Exercises on Reducing Pain Scale in Midwifery DIII Students at Paluta Husada Gunungtua - Umi Istiqomah (PT Inovasi Pratama Internasional, 2026)
Adolescence is a phase of life between childhood and adulthood, from the age of 10 to 19 years. Adolescence is a unique stage of human development and is an important time to lay the foundation for good health. This study is a quantitative type with a pre-experimental design that uses the one group pretest-posttest design, because this study aims to compare the results of the pretest of the intervention group and the posttest of the intervention group. The sample in this study were 66 students of the D-III Midwifery Study Program level I and II of STIKes Paluta Husada. Knowledge behavior before carrying out dysmenorrhea exercises had knowledge mostly in the sufficient category and after carrying out dysmenorrhea exercises knowledge was good, and before carrying out dysmenorrhea exercises students had a negative attitude because they felt it would not affect them, but after carrying out the exercises there was a positive attitude. D-III Midwifery Study Program students at STIKes Paluta Husada Gunung Tua can play an active role in helping to reduce menstrual pain problems, especially in female students with dysmenorrhea exercises. As midwifery students, we are expected to implement our role as midwifery care providers by regularly conducting dysmenorrhea exercises to reduce and manage menstrual pain